2019
DOI: 10.31646/gbio.44
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control in a treatment centre during a Lassa fever outbreak in southeastern Nigeria - January, 2018

Abstract: Introduction: Lassa fever (LF) is a communicable viral haemorrhagic disease. Person-to-person spread occurs by inhalation or direct contact with the bodily fluids of an infected patient. Infection Prevention and Control (IPC) is essential in healthcare facilities for the wellbeing and safety of patients, staff and visitors. Federal Teaching Hospital, Abakaliki is the designated treatment center for LF in Ebonyi State. We assessed IPC practices in this facility during the 2018 outbreak of LF involving healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Routine assessment of health systems is key to improving healthcare services delivery through identifying strengths and weaknesses and working towards fixing identified weaknesses. In our study location, there was an initial assessment of IPC which identified gaps during the nosocomial outbreak in 2018 (8,9). Several interventions had been carried out in the hospital to improve IPC after the initial assessment, and the hospital management in conjunction with her partners had organized series of training on IPC among its health workforce.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Routine assessment of health systems is key to improving healthcare services delivery through identifying strengths and weaknesses and working towards fixing identified weaknesses. In our study location, there was an initial assessment of IPC which identified gaps during the nosocomial outbreak in 2018 (8,9). Several interventions had been carried out in the hospital to improve IPC after the initial assessment, and the hospital management in conjunction with her partners had organized series of training on IPC among its health workforce.…”
Section: Discussionmentioning
confidence: 99%
“…A self-administered questionnaire was used to collect information from each respondent. The questionnaire was adapted from previous studies (9,12), and consisted of 4 sections. Section A obtained data on the sociodemographic characteristics of the respondents.…”
Section: Study Instrument and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations